2022
DOI: 10.1038/s41467-021-27867-4
|View full text |Cite
|
Sign up to set email alerts
|

Linking DNA repair and cell cycle progression through serine ADP-ribosylation of histones

Abstract: Although serine ADP-ribosylation (Ser-ADPr) by Poly(ADP-ribose)-polymerases is a cornerstone of the DNA damage response, how this regulates DNA repair and genome stability is unknown. Here, we exploit the ability to manipulate histone genes in Dictyostelium to identify that ADPr of the histone variant H3b at S10 and S28 maintains genome stability by integrating double strand break (DSB) repair with mitotic entry. Given the critical requirement for mitotic H3S10/28 phosphorylation, we develop separation of func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…We provide evidence for a direct interference between ADPr and phosphorylation on H3S10 and the same likely applies to H3S28 because those two residues are the main targets of damage-induced ADPr 21 . Notably, a similar interplay between H3S10/28 ADPr and phosphorylation was recently reported in response to DNA double-strand breaks in amoeba, impacting mitotic entry of cells with unresolved damage 26 . Regarding newly synthesized H3, we suspect that they impair H3S10ph because they may represent poor substrates for Aurora B due to their specific PTM pattern.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…We provide evidence for a direct interference between ADPr and phosphorylation on H3S10 and the same likely applies to H3S28 because those two residues are the main targets of damage-induced ADPr 21 . Notably, a similar interplay between H3S10/28 ADPr and phosphorylation was recently reported in response to DNA double-strand breaks in amoeba, impacting mitotic entry of cells with unresolved damage 26 . Regarding newly synthesized H3, we suspect that they impair H3S10ph because they may represent poor substrates for Aurora B due to their specific PTM pattern.…”
Section: Discussionsupporting
confidence: 64%
“…To directly and unambiguously address the crosstalk between ADPr and phosphorylation on the H3S10 residue, we introduced in U2OS cells non- ADPribosylatable forms of SNAP-tagged H3.1 or H3.3 by mutating S10 to a threonine (Figure S4F). Importantly, H3T10 can still be phosphorylated in early mitosis, as detected with an antibody that recognizes phosphorylation on both H3S10 and H3T10 26 . While a decrease in H3S10ph in response to UV irradiation was observed on endogenous histone H3 and on wild- type SNAP-tagged histones, as expected, the signal was unchanged on non-ADPribosylatable histone mutants (Figure 3D), indicating that UV damage-induced ADPr on H3S10 blocks the phosphorylation of this residue in early mitotic chromatin.…”
Section: Resultsmentioning
confidence: 99%
“…DNA double-strand breaks are among the most serious types of DNA damage [ 18 ]. γ -H2AX, formed after the phosphorylation of the histone H2AX, is closely associated with—and can be used as a marker of—DNA double-strand breaks [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…M. F. Langelier et al reported that HPF1 binds to PARP1 and PARP2 and inserts a Glu residue to complement the active site; furthermore, there are hydrogen/deuterium exchange mass spectrometry (HXMS) data that support the PARP1/HPF1 interaction in a dynamic manner ( Langelier et al, 2021) . A study on bacteriocelta showed that H3S10/S28 ADPr is required to inhibit mitotic entry during DNA damage ( Brustel et al, 2022 ). The PARP1/2-HFP1 complexes will redefine the role and significance of mono-ARTs in DNA damage and relevant cell biology.…”
Section: Location and Functionmentioning
confidence: 99%